A REVIEW ON PCOD IN PREGNANT WOMEN (World Journal of Current Medical and Pharmaceutical Research, 2019)
During the pregnancy time most of the pregnancy women suffering with various disorders. On that polycystic ovary syndrome (PC0S) plays a major role. If a pregnant women having polycystic ovary syndrome (PCOS) it shows various pathophysiological changes in pregnant women. According to world health organization PCOS is the commonest cause of an ovulatory infertility